Food and Consumer Attitude(s): An Overview of the Most Relevant Documents - Vítor João Pereira Domingues Martinho (Agriculture, 2021)
Food markets have, at least, two dimensions. One is related to supply, where food marketing, for example, plays a determinant role, namely to promote healthy and balanced consumption. The other dimension is associated with demand, where it is important to understand and bring insights about consumer attitudes, because they have implications on patterns of food consumption. In this framework, the main objective of this research is to suggest an alternative approach for conducting systematic reviews based on bibliometric analysis and implement it on topics about food and consumer attitudes. For this purpose, the most important bibliographic items (authors, sources, organizations, countries and documents) were identified and later the most relevant documents were reviewed. In addition, 908 documents were selected on 11 December 2020 from the Web of Science Core Collection, for the topics “food” and “consumer attitude*”, and analyzed through bibliometric analysis with the support of the VOSviewer and Gephi software. These documents were also benchmarked with those available in the Scopus scientific database. The approach presented here made it possible to highlight the main insights from the scientific literature related to consumer attitudes to food and bring about further contributions to a literature review supported by bibliometric analysis. This proposal may be known as MB2MBA2 (Methodology Based on Benchmarking of Metadata, from scientific databases, and Bibliometric Assessment and Analysis). This systematic review highlights that organic foods, food neophobia, climate change, marketing strategies and interrelationships between motivations–consumer attitudes–perceptions–purchase intentions–purchase decisions (MAPID) deserved special attention. In addition, MAPID interactions are impacted, among other dimensions, by labelling, branding and trust in the information provided. Future research should further address impacts on consumer attitudes towards food, such as those related to climate-smart agriculture, food 4.0, food security and protection, and climate change and malnutrition.